HUBUNGAN ANTARA EKSPOR, FDI, DOMESTIC CREDIT, DAN GDP DI NEGARA-NEGARA TIMUR TENGAH - Adam Surojo (CALYPTRA, 2018)
This research was conducted with the aim to know the relationship between Export, Foreign Direct Investment, Domestic Credit to Private Sector and Gross Domestic Product in Middle East countries during the period of 2004 - 2015, with countries sampled in this research as five countries namely Saudi Arabia, Kuwait, Iraq, Bahrain, and Qatar. Analytical method used is with Unit Root Test - PP and Granger Causality Test by using analysis tool to help process data is program Eviews 6. While the data used is time-series data from each of the five countries of Middle East which covers a period of 12 years. The analysis shows that FDI has a causal relationship with GDP in Saudi Arabia and Iraq. Domestic Credit to Private Sector has a causal relationship with FDI in the State of Iraq. FDI has a causal relationship with Domestic Credit to Private Sector in the State of Kuwait and Bahrain. While in the State of Qatar there is no causal relationship between variables.